New approach to electrode kinetic measurements in square-wave voltammetry: amplitude-based quasireversible maximum. - Mirceski, V; Laborda, E; Guziejewski, D; Compton, R (2013)
The influence of the potential pulse height of square-wave voltammetry (SWV) (i.e., the SW amplitude) is studied for a variety of quasireversible electrode mechanisms, including a simple solution-phase electrode reaction at a planar or spherical electrode, a solution phase electrode reaction coupled with a reversible follow-up chemical reaction, and a diffusionless surface confined electrode reaction. The electrode kinetics of all the electrode mechanisms depends critically on the SW amplitude, and the quasireversible kinetic region is a function of both frequency-related electrode kinetic parameters and the SW amplitude. Thus, a novel methodology for electrode kinetics measurements is proposed by altering the SW amplitude only, at a fixed frequency of the SW potential modulation, that is, at a constant scan rate of the voltammetric experiment. Electrode kinetic measurements at a constant SW frequency are of exceptional importance especially when complex electrode mechanisms are studied, which depend on several frequency-related kinetic parameters. The electrode kinetic measurements are based on a novel feature termed the "amplitude-based quasireversible maximum", manifested as a parabolic dependence of the amplitude-normalized net SW peak current versus the SW amplitude. The position of the amplitude-based quasireversible maximum depends on the standard rate constant of the electrode reaction, enabling estimation of this important kinetic parameter in a simple and fast procedure. The novel quasireversible maximum is attributed to all studied electrode mechanisms, implying that it is a general feature of most electrode mechanisms under conditions of SWV.